Perubahan Nilai Daya Dukung Tanah Lempung Lunak Akibat Stabilisasi Tanah menggunkaan Metode Deep Soil Mixing Pola Panels dengan Kapur 8% - Sadil, Salsabila Atalia; Iswan, Iswan; Syah, Aminudin (Universitas Lampung, 2021)
Palembapang, South Lampung requires proper road construction for public transportation needs. However, the road conditions in the village were found heavily damaged because of poor soil conditions. Therefore, soil stabilization must be carried out. The method of this study is deep soil mixing (DSM), which is soil improvement method by mixing additional materials in the field (in-site). This method is more affordable because they use their soil as theiraggregate and reduce the transportation budget because of stuff supply.The purpose of this study is to determine the change of soil load-bearing capacity due to the variation of distance and the diameter of the DSM stabilization column on soft clay soil and soft clay soil with 8% lime. This study shows that the stabilization of soft clay soil with 8% lime has increased its load-bearing capacity (qu) from 10.368 kg/cm2to 14.69 kg/cm2. The increase of soil load-bearing capacity with the stabilization of the DSM column is proportional to the volume of soil improvement. The largest increase of the soil load-bearing capacity occurred in 1D columns range and 3.75 cm diameter. The distance variation also gives a more significant change compared to the variation of diameter. The most efficient distance and diameter are at the variation of the distance of 1.25D columns range and 2.5 cm diameter.